2020
DOI: 10.1016/j.xpro.2020.100212
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput drug screening of fine-needle aspiration-derived cancer organoids

Abstract: Summary Generation of fine-needle aspiration (FNA)-derived cancer organoids has allowed us to develop a number of downstream applications. In this protocol, we start with organoids cultured in a semi-solid format. We dissociate organoids into single cells and then plate in a 384-well format for high-throughput drug screening. While this method must be fine-tuned for each individual organoid culture, it offers a format well suited for rapidly screening medium-sized drug/compound libraries (500–5,000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…For instance, the generation of hypoimmunogenic hiPSCs solicited T-cell and macrophage responses [Votanopoulos et al, 2020]. They used RNA interference and antibody to block the expression of HLA class I, which resulted in alleviated immune rejection and engraftment survival in both xenogeneic and allogeneic settings [Bergdorf et al, 2020;Votanopoulos et al, 2020]. More recent advances utilized genetic engineering to create hypoimmunogenic stem cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the generation of hypoimmunogenic hiPSCs solicited T-cell and macrophage responses [Votanopoulos et al, 2020]. They used RNA interference and antibody to block the expression of HLA class I, which resulted in alleviated immune rejection and engraftment survival in both xenogeneic and allogeneic settings [Bergdorf et al, 2020;Votanopoulos et al, 2020]. More recent advances utilized genetic engineering to create hypoimmunogenic stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…A gentler extraction technique can be also developed to enhance the half-life of immune cells in PTOs. Bergdorf et al developed a fine-needle aspiration method to extract PTOs, and results showed enhanced immune cell count, viability, and survival compared to conventional digestion methods [Bergdorf et al, 2020]. Assembloid models mostly focused on brain research, and limited studies have applied this technique to other contexts such as cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the use of FNA provides a promising methodology for translational and clinical cancer research. 15,[25][26][27][28]…”
Section: Fine-needle Aspiration: a Minimally Invasive And Cost-effect...mentioning
confidence: 99%
“…Their study emphasizes the potential of routine clinical FNA‐based collection techniques as a substantial source of material for generating tumor organoids from diverse tumor types for both clinical and discovery applications. Therefore, the use of FNA provides a promising methodology for translational and clinical cancer research 15,25–28 …”
Section: Fine‐needle Aspiration: a Minimally Invasive And Cost‐effect...mentioning
confidence: 99%
“…However, establishing distinct culture and assay conditions for each distinct tumor entity and constant supply of patient material for large screens remain a major challenge in using this combined targeted phenotypic approach with patient-derived organoids ( Boehnke et al, 2016 ). Efficient establishment of organoid cultures for different entities, drug assays including initial seeding material and density, treatment regimen, assay reproducibility, evaluation of drug response (e.g., IC50, area-under-the curve, Z-score IC50), drug validation, and assay scalability remain technical constraints and all need to be optimized ( Boehnke et al, 2016 ; Phan et al, 2019 ; Bergdorf et al, 2020 ) In addition, potential off-target toxicity cannot be assessed by organoid monocultures ( Pfohl et al, 2021 ). Nevertheless, patient derived organoids are a powerful tool which can be further expanded to take the tumor microenvironment into account, known to impact drug response, through suitable co-culture systems with e.g., cancer associated fibroblasts or immune cells ( Tsai et al, 2018 ).…”
Section: Combined Targeted Phenotypic Approach Utilizing Patient Derived Organoids—a Promising Strategy For Pdac Treatment Developmentmentioning
confidence: 99%